MANUSIA DALAM SOROTAN AL-QUR’AN (SUATU TINJAUAN TAFSIR MAUDHUI) - Roswati Nurdin (IAIN Ambon, 2017)
This paper describes the concept of humans in the Qur'an that were examined by the method of thematic(maudhui). Subject matter includes concepts and functions of human beings, both as individuals and communities. Searching the nature of man is not only based on subjective view, which resulted in the issue of human nature becomes blurred. As a result of the creation work, the issue should not be studied apart from the human point of view of its creators to acquire comprehensive knowledge. If this is accepted- examine the human perspective on its creator -the only way to get to know who the man was referring to the divine revelation, so that the answer can be found. To this effect, certainly not enough to simply refer to one or two verses, but it should refer to all the verses of the Koran (or at least the primary verses) that talks about the issues, the learning context, respectively, and for the affirmation - kind of Prophet explanation, or facts that have been scientifically established. This way are known in the Qur'an disciplines as maudhuiy methods (thematic) Keywords: The Human, the Qur’an, thematic method